Analisis Sistem Kolaborasi Lembaga Kemasyarakat Desa - Ade Wahyuni Azhar; Aqila Nasya Ramadhani (Institut Riset dan Pengembangan Indonesia, 2024)
The internal collaboration of the Bulu Cina Village Government and the Lembaga Kemasyarakatan Desa (LKD) (LKD) has a positive impact on the progress of the welfare of the village community. The involvement of community actors and communities at the local level is a strategic step in the management of village funds to provide transparent and accountable effects, as mandated by the collaborative governance model so that the results of development become more beneficial to the people of Bulu Cina Village. This research uses a qualitative method. The technique of taking informants is carried out by snowball sampling while maintaining independence in expressing opinions. Data collection methods with in-depth interviews, observation and analysis of documents. Data analysis was carried out interactively, starting from data collection, data condensation, data display, and research conclusions that were drawn and combined with descriptive data display. The results of the study show that the collaborative process has not gone well, as can be seen from the election of LKD administrators is still based on the appointment of the Village Head and does not have representation from each hamlet. However, as time goes by, there has been an understanding between the government of Bulu Cina Village and the Lembaga Kemasyarakatan Desa (LKD).